Geochemistry and origin of the Neoproterozoic Natkusiak Flood Basalts and related Franklin Sills, Victoria Island, Arctic Canada - Beard, Charles; Scoates, James; Weis, Dominique; Bedard, Jean; Dell'Oro, Trent (EarthArXiv, 2018)
The Natkusiak continental flood basalts and Franklin sills of Victoria Island preserve an exceptional record of the ca. 716–723 Ma Franklin large igneous province and are synchronous with major climatic variations and breakup of the supercontinent Rodinia. The Natkusiak Formation basalts record an early phase of discontinuous rubbly flows (<100 m, low-Ti Type 1 magmas) overlain by a thicker series of extensive tholeiitic sheet flows (~1100 m, high-Ti Type 2 magmas). Coeval intrusions hosted by underlying Shaler Supergroup sedimentary rocks are differentiated low-Ti Type 1 Franklin sills and doleritic high-Ti Type 2 sills, both of which show correlations in isotope plots with the northernmost basalts on Victoria Island. Whole-rock Pb-Sr-Nd-Hf isotopic compositions from 66 samples indicate that the earliest magmas (Type 1) had similar primary melt compositions (Fo90 olivine) to oceanic island basalts and incorporated up to 10% granitoid basement (initial eNd = –0.8 to –7, Nb/La = 0.42 to 0.67), a relatively weak continental signature compared to many other continental flood basalt provinces. Type 2 doleritic sills and the northern sheet flow basalts incorporated up to 5% granitoid (initial eNd = +0.9 to +5.5), consistent with a waning continental influence during maturation of the magmatic system. Radiogenic isotope ratios are not correlated with indices of fractional crystallisation, which indicates that the continental material was either dispersed within the melt source, or that magmas were heterogeneously contaminated prior to differentiation. In the southwestern part of Victoria Island, Type 1 basalts show negligible continental influence (Nb/La = 0.81 to 0.94) and have unusually high initial eNd ratios (+4.4 to +11.8) that are decoupled from initial eHf (+0.8 to +11.1). These radiogenic eNd compositions persist throughout the southern volcanic stratigraphy and indicate involvement of a component with high time-integrated Sm/Nd that lacked correspondingly high Lu/Hf. We suggest that the source region for the southwestern Natkusiak basalts and related sills included isotopically matured oceanic crust, which was recycled through the asthenospheric mantle into a laterally heterogeneous plume. The distinct trace element signatures of the southern and northern sources became attenuated with the onset of voluminous melting (corresponding to emplacement of the Type 2 doleritic sills and sheet flow basalts) and may reflect contributions from hydrous eclogitic material emplaced into the lithospheric mantle during the ca. 1.9 Ga Wopmay Orogeny. As both the northern and southern volcanic rocks exhibit contrasting isotopic signatures throughout the preserved stratigraphy, the magma plumbing system must have limited lateral mixing and homogenisation, which allowed for the expression of distinct mantle source signatures in the high-level sills and basaltic lavas.